Kedudukan Konstitusional Menteri Triumvirat Sebagai Pelaksana Tugas Kepresidenan Dalam Sistem Pemerintahan Presidensisil di Indonesia - Titik Triwulan Tutik (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2020)
Amendments of the 1945 Constitution reinforce the declaration of the rule of law, also clearly stipulating the presidential system of government. The manifestation of the presidential system is that the position of ministers is very important. Because basically the ministers are the leaders of the government (pouvoir executief) in the true sense in their respective fields of duty. It is the minister who determines the politics of government and coordination in the administration of the State. The existence of ministers of the Indonesian constitutional system is getting stronger with the recognition of three ministerial positions called triumvirate ministers. The three ministerial positions are the Minister of Home Affairs, the Minister of Foreign Affairs, and the Minister of Defense, which is regulated separately in Article 8 paragraph (3) of the 1945 Constitution. If the situation of vacancies in the positions of President and Vice-President together at the same time truly occurs, then there may be various legal issues related to the three ministerial positions. For example, there could be a dispute between the three, about who is more authorized among them, and even between the three of them as one entity with other institutions. If that happens the dispute can only be resolved legally by the Constitutional Court in accordance with its duties and authorities. Perubahan UUD 1945 mempertegas deklarasi negara hukum, juga menetapkan dengan jelas mengenai sistem pemerintahan presidensiil. Wujud dari dainutnya sistem presidensisil adalah bahwa kedudukan menteri-menteri sangat penting. Karena pada dasarnya para menteri itulah yang menjadi pimpinan pemerintahan (pouvoir executief) dalam arti yang sebenarnya di bidang tugasnya masing-masing. Menterilah yang menetapkan politik pemerintahan dan koordinasi dalam pemerintahan Negara. Keberadaan menteri sistem ketatanegaraan Indonesia semakin kuat dengan dikenalnya tiga jabatan menteri yang disebut dengan menteri triumvirat. Ketiga jabatan menteri tersebut adalah Menteri Dalam Negeri, Menteri Luar Negeri, dan Menteri Pertahanan yang diatur tersendiri dalam Pasal 8 ayat (3) UUDNRI 1945. Menteri triumvirat inilah yang menggantikan kedudukan Presiden dan Wakil Presiden mangkat, berhenti, diberhentikan, atau tidak dapat melakukan kewajibannya dalam masa jabatannya secara bersamaan. Apabila keadaan kekosongan dalam jabatan Presiden dan Wakil Presiden secara bersamaan sungguh-sungguh terjadi, maka dapat saja timbul berbagai persoalan hukum yang terkait dengan ketiga jabatan menteri tersebut. Misalnya bisa saja terjadi sengketa antara ketiganya, tentang siapa yang lebih berwenang di antara mereka, dan bahkan antara mereka bertiga sebagai satu kesatuan dengan lembaga lain. Bila hal tersebut terjadi, maka secara yuridis penyelesaian sengketa tersebut hanya dapat diselesaikan secara hukum oleh Mahkamah Konstitusi sesuai dengan tugas dan wewenangnya.